1891 Just another paperwork exercise? A one year review of an emergency department adolescent safeguarding meeting. (15th December 2022) - Roberts, Zoe; Green, Lisa; Lloyd, Fionn; Lee, Vicky; Foley, Harriet; Cordery, Lisa; Pugh, Claire; Wakefield, Diana; Wescombe, Karen
Abstract : Objectives: To review outcomes of young people, identified through screening of 'red flag' presentations, discussed at an Emergency Department (ED)-focussed Adolescent Safeguarding meeting Background: At the University Hospital of Wales (UHW) in Cardiff, young people aged 16 & 17 years presenting to the ED will be seen and managed within the adult unit, unless under ongoing care of a Paediatrician. In September 2018, focus groups were set up during the participation phase of the Trust's Children's Charter, where users of the service gave feedback on their ED experience. The results, and a subsequent snapshot audit assessing safeguarding (SG) issues arising within this transitional age group, highlighted a significant need to offer equity of safety-net processes, reflecting those afforded to younger children attending the Paediatric ED. A multi-agency task group convened to understand the issues and address the shortcomings. A series of changes followed, including adolescent specific paperwork, incorporating the HEADS screening tool and associated pathway, plus the introduction of a bi-weekly 'Adolescent Safeguarding' meeting. Here, 'red flag' cases* are reviewed by representatives from Violence Prevention, Emergency Medicine, Safeguarding, Department of Sexual Health (DOSH), Child & Adolescent Mental Health Services (CAMHS), Frequent Attenders (FA), Childs Rights Advocate and Looked After Children (LAC) teams, gaps identified and relevant referrals made. Methods: A retrospective review of the cases discussed at the Adolescent Safeguarding meeting from 01.03.2021 until 28.02.22 was undertaken. Outcomes were reviewed, primarily to assess the frequency of onward referrals. * red flag attendances include: assault/punch injuries mental health (e.g Overdose/DSH) UTI/genitourinary Pregnancy/sexual health Abdominal pain Drugs/alcohol Looked after young person Results: Sixteen & seventeen year-olds made up 2968 attendances during the year, with 727 (24%) requiring discussion at the SG meeting, flagged from their presenting complaint (average 30 cases per meeting). Of those discussed, 305 (42%) required referral to another service with an average of 12 referrals made per meeting. Referrals included: Conclusions: Almost a quarter of 16 & 17 year olds attending the adult ED at a large tertiary hospital presented with potentially high risk complaints. Of these, almost half were felt retrospectively to require further support by way of onward referral, with the majority to Children's Services. Whilst the processes are largely in place locally to support, educate and inform at time of presentation, this age group continue to slip through the gap. The adult service remains overwhelmed, 'child-specific' legislation may be overlooked and frequently only physical symptoms are identified and treated. Much work is being done to address these challenges, including education of staff, digitalised referral processes and consideration of recruiting allied professionals, such as Youth Workers, to work within the ED. Making every contact count at point of presentation is clearly the gold standard, however, the Adolescent Safeguarding meeting provides some reassurance of safety netting for this vulnerable group of patients.